Does Africa trade less than it should, and if so, why?: The role of market access and domestic factors - Bouët, Antoine; Mishra, Santosh; Roy, Devesh (International Food Policy Research Institute, 2008)
This paper addresses the question of whether Africa is an undertrading continent. We answer this question using a much-improved data set for obtaining predicted trade and by employing methods that correct for bias in estimates of undertrading. Our results indicate that globally Africa is an underexporter in our preferred Heckman specification. This result is robust to the addition of various controls and the application of variants of the gravity model of trade. We also looked for explanations for Africa's undertrading. We found that accounting for transport and communication infrastructure reduced the undertrading effect for Africa, and in some specifications of the gravity model, the under-trading effect vanished altogether. Results from a semiparametric model provided evidence of significant nonlinear impacts from infrastructure, and the effects for a large number of African countries was significant and compared favorably with the marginal effects of infrastructure in countries on other continents and in comparable income brackets. Using this model we also found evidence of complementarity across transport and communication infrastructure, implying that much greater impacts will be likely if the infrastructure are developed jointly rather than in isolation.